Managing human activity and marine mammals: A biologically based, relativistic risk assessment framework - Southall, Brandon L.; Tollit, Dominic; Amaral, Jennifer; Clark, Christopher W.; Ellison, William T. (Frontiers in Marine Science, 2023)
Presented here is a broadly applicable, transparent, and repeatable analytical tool for assessing relative risk levels for marine species exposed to anthropogenic disturbances, including specific examples of its application to the installation of simulated offshore wind farms. The objectives are to provide managers and action-proponents tools with which to objectively evaluate and dissect the principal activities (and data gaps in evaluating) that drive potential biological risk and to identify actionable measures to reduce that risk. Current regulatory assessments of how a human activity (particularly those that produce noise) influences marine animal behavioral responses and increases the likelihood of potential injury rely principally on generalized characterizations of exposure and effect using simple, threshold-based criteria. Although well-structured in regulatory application, this approach fails to adequately address realistic site and seasonal scenarios, other potential stressors, and scalable outcome probabilities. The risk analysis presented here is primarily based on a common and broad understanding of the spatial-temporal-spectral intersections of animals and anthropogenic activities. The resulting species- and activity-specific framework parses risk into two factors: a population’s innate ‘vulnerability’ (potential degree of susceptibility to disturbance) and an ‘exposure index’ (magnitude-duration severity resulting from exposure to the activity). The classic intersection of these two multi-dimensional factors provides a comparative risk assessment process for realistic evaluation of specified activity contexts, sites, and schedules, convolved with the seasonal presence and behavior of potentially affected species. This process is inherently scalable, allowing relativistic means of assessing animal distribution and potential disturbance scenarios, tuned to variable contexts, areas, and degrees of spatial resolution.